Hemodialysis Patients’ Satisfaction and Associated Factors in National Teaching Hospital Hemodialysis Center, Cotonou (Benin) - AGBOTON, BRUNO (My University, 2019)
Background: Patients’ satisfaction is a relevant component in assessing healthcare services. The objective of this study was to study the level of satisfaction of chronic hemodialysis patients and the associated factors in Cotonou CNHU-HKM dialysis center. Patients and Methods: It was a cross-sectional, descriptive and analytical study conducted by administering a questionnaire on days off dialysis. It was carried out from 1st November 2015 to 1st January 2016 in CNHU-HKM Nephrology University Clinic of Cotonou. Hemodialysis patients aged 18 years and above having given their informed consent were included in the study. Patients’ recruitment was comprehensive. Likert scale was used in assessing the level of satisfaction with 4 as “very satisfied” and 1 for “very dissatisfied”. Satisfaction was evaluated on the basis of Ware dimensions. The threshold for satisfaction was 50. Outcomes: Overall, 377 patients were included in the study. Respondents’ mean age was 51.5 ± 13.3 years with 1.37 as sex ratio. Arteriovenous fistula was used for 80.1% of hemodialysis patients. 77.7% of the patients underwent dialysis twice a week while 45.9% were administered a four-hour dialysis. The overall average proportion of “satisfied” was 76.5%. The level of satisfaction was 52% for healthcare environment, 61% for service delivery, 73.9% for healthcare accessibility, 76.1% for healthcare structure, 77.5% for healthcare management, 90.3% for quality of healthcare, 88.3% for interpersonal relationship and 93.2% for efficiency and continuum of healthcare. Factors associated with satisfaction included age (p = 0.02), vascular access (p = 0.04) and urea reduction ratio (p = 0.01). In addition, the degree of satisfaction of hemodialysis patients was not statistically associated with sex, marital status, educational level, history of the disease, age of dialysis, number of sessions per week, and duration per session. Conclusion: The overall level of hemodialysis patients’ satisfaction is above average. There is a need to particularly focus on healthcare environment, so as to better improve the level of satisfaction.
Keywords: Satisfaction; Chronic Hemodialysis; Cotonou